Digitalization of logistics processes and the human perspective - Adina Silvia Kuhlmann; Matthias Klumpp (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
This contribution presents an analysis of the increasing consequences of digitalization with a focus on self-monitoring of personnel in logistics and production processes. This is of interest as digitalization requires large-scale innovative implementation and change management approaches in logistics and production processes. Based on standard DIN ISO 10.075 ('risk assessment') an applicationoriented instrument is developed to evaluate und test new job systems, which are impacted by digitalization. This enables the development of digitalization strategies and an option analysis for further digitalization investments based on human workforce orientation. Furthermore, individual concepts for recruiting and selecting qualified personnel for digital job systems could be derived. Such an application-oriented risk assessment tool has the goal of analyzing the increasing digitalization concerning the self-monitoring of personnel and delivers options for the organization and formation of job systems in production and logistics. Afterwards, additional measures for innovative digital job systems for SCM processes and tasks can be derived. These additional measures can also be transferred to other industries in the service sector. This contribution presents first results concerning an in-depth document analysis based on DIN ISO 10.075 in comparison with existing logistics research literature and business practice knowledge.
urn:nbn:de:gbv:830-88217778; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; digitalization; risk assessment; change management; mental stress